Magnetic Susceptibility and molecular Structure; Study of Uranyl Complexes with Schiff Bases of 2-Hydroxy-1-Naphthaldehyde and Some Aryl Amines - Dodwad, S.S. (Asian Journal of Chemistry, 2012)
Uranyl Complexes of some Schiff bases obtained by condensing some aryl amines with 2-hydroxy-1-nephthaldehyde are synthesized and characterized by elemental analysis, spectral and conductivity data. All the complexes are orange-red to red in color, microcyrstalline in nature and form compound of the type [UO2(LH)2](CH3COO)2 where (LH) is a Schiff base molecule. The bonding with the metal in the complexes takes place from hydroxyl oxygen and imine nitrogen of the ligand. It is observed that uranyl ion form 1:2 adducts with these Schiff bases. Conductivity measurements, analytical data and spectral study show that these complexes have co-ordination number eight with hexagonal bipyramid structure. All the complexes studied are spin paired, since they exhibit property of diamagnetism. Diamagnetism of complexes is discussed.